Guia de laboratorio virtual para la simulación y control de movimientos de un brazo robótico (2021)
This project was based on how the experimental resources of a university laboratory, focused on the career subjects of the Faculty of Mechanical, Electronic and Biomedical Engineering (FIMEB), of the University Antonio Nariño, help to strengthen the knowledge and put into practice the theory learned in the subjects of robotics, control, linear algebra among others, through the development of a Virtual Laboratory, which, with the help of a graphical interface in MATLAB, will allow the student to interact with the platform, thus ensuring a better academic development, since the laboratories at the time of this degree work, could not be developed in person, given the restrictions decreed by the National Government of Colombia as a result of the SARS-COVID-19 pandemic. But thanks to ICT (Information and Communication Technology) and its novel communications and learning features, such as the Internet, video conferencing, instant messaging, telepresence and simulation.